Survey on segmentation of liver from CT images - Priyadarsini, S.; Selvathi, D. (2012 IEEE International Conference on Advanced Communication Control and Computing Technologies, 2012)
Liver cancer is one of the most popular cancer diseases and causes a large amount of death every year. The chances for liver cancer in men and women have increased to 40% and 23% respectively. Segmentation of liver from images of the abdominal area is critical for diagnosis of tumor and for surgical procedures. Accurate detection of the type of the liver abnormality is highly essential for treatment planning which can minimize the fatal results. Accurate results, however, can be obtained only through computer aided automated systems. Besides being accurate, these techniques must converge quickly in order to apply them for real time applications. Many reports claim its work to be superior, but a complete comparative analysis is lacking in these works. In this survey paper, an extensive comparative analysis is performed to illustrate the merits and demerits of various available techniques. This work also explores the applicability of the techniques in liver segmentation from Computed Tomography images. The main objective of this work is to highlight the position of various automated techniques which can indirectly aid in developing novel techniques for solving the health care problem of the medical sector.